2005
DOI: 10.4049/jimmunol.175.8.5058
|View full text |Cite
|
Sign up to set email alerts
|

Both Regulatory T Cells and Antitumor Effector T Cells Are Primed in the Same Draining Lymph Nodes during Tumor Progression

Abstract: The peripheral tolerance mechanism prevents effective antitumor immunity, even though tumor cells possess recognizable tumor-associated Ags. Recently, it has been elucidated that regulatory T cells (Treg) play a critical role in maintaining not only self-tolerance, but also tolerance of tumor cells. However, because the Treg that maintain self-tolerance arise naturally in the thymus and are thought to be anergic in peripheral, it is still unclear where and when Treg for tumor cells are generated. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 36 publications
7
72
1
Order By: Relevance
“…29,44 Furthermore, murine studies have demonstrated that Treg responses develop parallel to Th responses as a feedback mechanism to control the size of the immune response, 45 which takes place in the same draining lymph node. 46 Isolated Tregs from chronic HCV patients inhibited HCV specific CD8 1 T-cell responses but also peptide-specific CD8 1 CTL responses against other viruses. 40, 42 Here, we found no correlation between Treg frequencies and CTL, by comparing Treg frequencies between patients who had detectable HPV16 E6E7 specific CTL in the peripheral blood and patients who were negative for HPV16 E6E7 specific CTL.…”
Section: Discussionmentioning
confidence: 99%
“…29,44 Furthermore, murine studies have demonstrated that Treg responses develop parallel to Th responses as a feedback mechanism to control the size of the immune response, 45 which takes place in the same draining lymph node. 46 Isolated Tregs from chronic HCV patients inhibited HCV specific CD8 1 T-cell responses but also peptide-specific CD8 1 CTL responses against other viruses. 40, 42 Here, we found no correlation between Treg frequencies and CTL, by comparing Treg frequencies between patients who had detectable HPV16 E6E7 specific CTL in the peripheral blood and patients who were negative for HPV16 E6E7 specific CTL.…”
Section: Discussionmentioning
confidence: 99%
“…Hiura et al recently reported that both Treg and antitumor effector T cells were primed in the same TDLN of a tumor growing subcutaneously. (12). PC61 mAb are usually injected a few days before or at the time of tumor cell implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversion of CD4 + CD25 À T cells into Treg seems rather common in tumordraining lymph nodes (TDLN; refs. [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It has been demonstrated that CD4 1 CD25 1 Treg cells are potent suppressors or regulators in controlling allergic responses, allograft rejection, antitumor immunity and microbial immunity, in addition to keeping self-tolerance. [5][6][7] It is now clear that forkhead family Foxp3 is a specific transcription factor of CD4 1 CD25 1 Treg cells, at least in mice. [8][9][10] Mutations in Foxp3 cause a similar X-linked recessive autoimmune and inflammatory disorder in humans and mice.…”
Section: Introductionmentioning
confidence: 99%